2020
DOI: 10.1038/s41467-020-15598-x
|View full text |Cite
|
Sign up to set email alerts
|

XPO5 promotes primary miRNA processing independently of RanGTP

Abstract: ✉ XPO5 mediates nuclear export of miRNA precursors in a RanGTP-dependent manner. However, XPO5-associated RNA species have not been determined globally and it is unclear whether XPO5 has any additional functions other than nuclear export. Here we show XPO5 pervasively binds to double-stranded RNA regions found in some clustered primary miRNA precursors and many cellular RNAs. Surprisingly, the binding of XPO5 to pri-miRNAs such as mir-17~92 and mir-15b~16-2 and highly structured RNAs such as vault RNAs is RanG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 45 publications
(98 reference statements)
0
17
0
Order By: Relevance
“…This suggests that similar to full length HST, this portion of the protein is necessary for miRNA accumulation but dispensable for miRNA nuclear/cytoplasmic movement. Mammalian EXP5 has recently been shown to be required for miRNA processing in a RAN GTPase-independent manner (Wang et al, 2020). By analogy, our data suggested that a potential export function of HST, if any, and its interaction with RAN1 are dispensable for miRNA movement from the nucleus to the cytoplasm, potentially allowing us to uncouple HST's presumed exportin function from its role in the miRNA pathway.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…This suggests that similar to full length HST, this portion of the protein is necessary for miRNA accumulation but dispensable for miRNA nuclear/cytoplasmic movement. Mammalian EXP5 has recently been shown to be required for miRNA processing in a RAN GTPase-independent manner (Wang et al, 2020). By analogy, our data suggested that a potential export function of HST, if any, and its interaction with RAN1 are dispensable for miRNA movement from the nucleus to the cytoplasm, potentially allowing us to uncouple HST's presumed exportin function from its role in the miRNA pathway.…”
Section: Resultsmentioning
confidence: 51%
“…HST is the plant ortholog of EXPORTIN 5 (EXP5/XPO5), and by analogy with animal systems, HST has been proposed to export miRNAs from the nucleus to the cytoplasm in plants (Brownawell and Macara, 2002). EXP5 also acts independently of its export activity by enhancing pri-miRNA processing efficiency of the DROSHA/DGCR8 microprocessor (Wang et al, 2020). Importantly, the assumption that HST is a miRNA exporter is based on expected functional homology between organisms but is not supported by experimental data, as the subcellular distribution of miRNAs between the nucleus and the cytoplasm is not altered in hst mutants (Park et al, 2005;Zhang et al, 2020;Zhu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Pre-miRNAs are transported through the nuclear pore and then released into the cytoplasm upon the hydrolysis of RanGTP to RanGDP. Intriguingly, exportin 5 has also been reported to promote pri-miRNA processing, which is independent of RanGTP [ 18 ].…”
Section: Biogenesis Of Mirnasmentioning
confidence: 99%
“…Accelerates pri-miRNA processing by DROSHA; in complex with SMAD4 activates miRNA precursor transcription upon TGFB/BMP signaling [72,124,125] Export to cytoplasm XPO5 (EXP5) Plays a role in the nuclear export of pre-miRNA to the cytoplasm [138,139]; facilitates the nuclear cleavage of clustered pri-miRNAs [140] RAN Interacts with XPO5; plays a role in the export of pre-miRNA to the cytoplasm [138] Cytoplasmic steps of miRNA biogenesis DICER1 (DICER) RNase III; catalyzes pre-miRNA to miRNA-duplex processing by cutting off the pre-miRNA terminal loop [11,[141][142][143] TARBP2 (TRBP) Coordinates pre-miRNA recognition by DICER1 and the precision of DICER1 cleavage [144,145] PRKRA (PACT)…”
Section: Smad2mentioning
confidence: 99%